Major factors affecting contemporary Japanese business environment. Issue 3 (2nd March 2015) - Blahová, Michaela; Haghirian, Parissa; Pálka, Přemysl
Abstract : Purpose: – The purpose of this paper is to investigate factors influencing contemporary Japanese business environment mainly in the field of strategic management and, therefore, having influence on corporate performance and its measurement in selected manufacturing companies located in Japan in respect to their key business perspectives focused on people, processes and systems, innovations, finance, social responsibility and ecology, and that in relation to ongoing economic crises and a fundamental transformation of mature societies (in particular in USA, Japan and Western Europe). Design/methodology/approach: – The research involved assembling key academic and other literature on the subject of trends in strategic management and performance measurement in Japan as well as semi-structured interviews with managers within manufacturing companies located in Japan that deal with performance measurement, finance, strategic management, etc. and a review of various internal management reports. Findings: – The research has been useful in identifying companies that respond to current changes and trends the fastest and the most effective. Research limitations/implications: – Among the limitations of the conclusions belongs rather a small sample of companies involved in the research. Moreover, the respondents may have seen their own company more favourably than an objective outsider would have done. Originality/value: – This paper shares insights on current trends influencing Japanese business environment and how these trends are implemented, used and updated in a selected sample of companies located in Japan.